Strategi Kerjasama Sipil-Militer dalam Pengelolaan Bandar Udara Antara PT Angkasa Pura II dengan Lanud Husein Sastranegara - Qadarsyah, Rindo; Soleh, Soleh; Ruselvi, Nanda (Prosiding Seminar Nasional Sains Teknologi dan Inovasi Indonesia (SENASTINDO), 2022)
The existence of an airport with flight facilities in it provides benefits for the movement of people and goods in terms of time. When examined more deeply, there are several problems with civil enclave airports, especially those that are used together in the Indonesian Air Force area, including the cooperation that has been made that has not optimally contained the security management system, which involves very few Indonesian Air Force personnel, in this case the local air base personnel. both in the operational activities of the flight and its security as well as the infrastructure used has not been integrated. The purpose of this study is to obtain some descriptions of the implementation of civil-military cooperation in the management and security of airports in order to improve the security of the current national airspace. This type of research uses a qualitative descriptive approach. In accordance with the data obtained by the researcher, the joint use of Husein Sastranegara Airport between the Indonesian Air Force and PT. Angkasa Pura II has been running smoothly and well, but is still constrained by the legal basis and regulations for cooperation between agencies that have not materialized. In addition, obstacles in the management of Husein Sastranegara airport include things that are not technically regulated in coordination in the field. A Letter of Operational Coordination Agreement (Loca) or Letter of Agrement (LOA) needs to be made in order to make an agreement on an activity. Inside Husein Sastranegara Airport there are several stakeholders, namely Customs, Immigration, Port Health Office. All of these stakeholders still do not have a binding cooperation agreement with the Indonesian Air Force, only in the form of coordination between agencies. The process of developing the Civil-Military Cooperation strategy in the management of Husein Sastranegara Airport needs to be focused on formulating a complete cooperation regulation that touches all stakeholders within the Husein Sastranegara Airport.